Analisis Audit Energi di Gedung Teknik Elektro Universitas Diponegoro - Diah Larasati, Pangestuningtyas; Fitrianti Sugiono, Friska Ayu; Arvin Karuniawan, Eriko; Karnoto (Universitas Nusa Putra, 2023)
An energy audit is a work that aims to identify energy consumption in buildings that have been built so that they can find opportunities for energy savings in these buildings and buildings and improve energy efficiency and conservation in these buildings. The Electrical Engineering Building is one of the buildings at Diponegoro University that has been built for a long time, and to find out the savings opportunities in the building, an energy audit is needed. The energy audit was carried out during the pandemic era where lectures were still being held online and hybrid. Based on the results of the energy audit that has been carried out, it was found that the Energy Consumption Intensity (IKE) in the Electrical Engineering Building in 2021 was 8.59 while in 2022 it was 12.61. This is still in the efficient category according to Regulation of the Minister of energy and mineral resources No. 13/2012. Opportunities for savings can be implemented starting from no cost, low cost, to high cost to increase the efficiency of energy use in the Diponegoro University Electrical Engineering Building, so that energy use can be very efficient.